EFEKTIVITAS KOMUNIKASI INTERPERSONAL TUTOR DAN MURID DI LEMBAGA KURSUS EASY SPEAK PEKANBARU - Windiyana Sari; Welly Wirman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Interpersonal communication is a very important in the learning process, and establishing a good relationship tutor and student in easy speak institutions courses Pekanbaru. With this interpersonal communication, the tutor can determine how to form a good relationship to students, causing a sense of passion and motivation to students in the following subjects and can speak English well. The purpose of this study is to explain how the effectiveness of interpersonal communication tutors and students in institutions of English courses Easy Speak Pekanbaru.The research was conducted in institutions of English courses Easy Speak Pekanbaru, which is located at Jalan Ahmad Yani, Pekanbaru. This study uses descriptive qualitative research methods that describe and interpret the data. Informants in this study are tutor and student, using purposive techniques. Data collection techniques by using observation, interviews and documentation.The results of this study indicate interpersonal communication tutors and students have been working effectively in institutions of English courses Easy Speak Pekanbaru. In this case, the effectiveness of interpersonal communication tutor and student, the tutor can provide knowledge, motivation, passion and know the characteristics of each student so that the students can speak English very well by considering five aspects: openness, empathy, positiveness, supportiveness and equality.